Empowerment on Chinese Police Force's Role in Social Service - Wang, Xiaohai; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2015)
This is the first scholarly book to explore the empowerment and the social service role of frontline police officers in the People’s Republic of China. It approaches the study of role strain and empowerment, informed by local empirical data and personal experience. Thematically organized and focusing on those issues of greatest concern to the public, such as the dual social control (informal and formal) mechanism, mass line policing, strike-hard campaigns, police professionalization and professional ethics, as well as the paramilitary-bureaucratic structure in the Chinese police organization, it provides a detailed discussion of these and other contemporary issues. The book offers a valuable resource for students and researchers in the area of comparative policing and comparative criminal justice, as well as police professionals and policy-makers.
Introduction -- Key Themes of Chinese Policing -- Theoretical Framework -- Methodology -- Policing in the Pre-reform Era: Mass Line of Policing -- Policing in the Reform Era: Strike Hard Campaigns and Emergence of Police Social Service Role Conflict and Incongruity -- Policing in the Reform Era: The Police Professionalization and Emergence of Police Social Service Role Ambiguity, Overload and Inadequacy -- Community Policing in the Reform Era: Police Professional Ethics and Emergence of Social Service Role Under-compensation -- Police Social Service Role Strain-Stress: Findings of Their Relationship and Rise of Formal Social Control -- Coping with Police Social Service Role Strain: Findings of the Paramilitary-Bureaucratic Structure and Structural Empowerment of the Police Organization -- Coping with Police Social Service Role Strain: Findings of the Paramilitary-Bureaucratic Structure and Psychological Empowerment of the Police Organization -- Conclusion -- Reference -- Appendices.
Keywords: Criminology; Sociology; Criminology and Criminal Justice, general; Sociology, general